2016
DOI: 10.1021/acs.analchem.5b04484
|View full text |Cite
|
Sign up to set email alerts
|

Robust Bayesian Algorithm for Targeted Compound Screening in Forensic Toxicology

Abstract: As part of forensic toxicological investigation of cases involving unexpected death of an individual, targeted or untargeted xenobiotic screening of post-mortem samples is normally conducted. To this end, liquid chromatography (LC) coupled to high-resolution mass spectrometry (MS) is typically employed. For data analysis, almost all commonly applied algorithms are threshold-based (frequentist). These algorithms examine the value of a certain measurement (e.g., peak height) to decide whether a certain xenobioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…The mass spectrometer was operated in positive electrospray mode with an acquisition at 70 000 resolving power. Further details can be found on Materials and Methods section of refs and for the two data sets, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrometer was operated in positive electrospray mode with an acquisition at 70 000 resolving power. Further details can be found on Materials and Methods section of refs and for the two data sets, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the chromatographic domain, the elution process of a given compound retained by the column of the system is usually summarized as having a Gaussian-like shape with a long tail, and thus, it is a common approach to use a Gaussian function as a representative mathematical model for feature detection. However, all factors affecting the peak shapes have not yet been fully characterized, so therefore, other mathematical models have also been proposed to represent chromatographic peaks . In most cases, the feature detection processes are approached either one dimensionally, by taking the chromatographic and MS space separately, or two-dimensionally, using three-dimensional models by taking into account both separation spaces simultaneously. , In our previous work, we have highlighted the benefit of using a multidimensional model to capture all common characteristics of an LC–HRMS data governed by a probabilistic framework. , In the second step of untargeted screening (ii), given the detected peak features from the first step (i), an exhaustive probabilistic assessment to identify a possible match between the detected features and any candidate compound that could explain the observed pattern should follow.…”
mentioning
confidence: 99%
“…A recent work by Taylor et al [1] demonstrated an artificial neural network (ANN) that was trained on two good quality reference EPGs to classify data in the 6-FAM dye lane and then applied to a third (also good quality) EPG with reasonable success. Taylor et al [1] provided a proof of concept that ANN could be used to interpret EPGs, which we extend here by: 1) Increasing the amount of training data 2) Increasing the range of training EPG quality from completely blank to highly overloaded 3) Improving on the architecture of the ANN used 4) Training a series of ANN that are used on different areas of the EPG 5) Coupling the predictions of the ANNs with a peak detection algorithm originally designed for LCMS data [2,3] and recently extended to DNA EPG data [4] to produce a peak detection and classification system Having created the peak detection and classification system we trial it on several profiles and demonstrate the results, which we compare to the peaks flagged by Genemapper® ID-X (Life Technologies).…”
Section: Introductionmentioning
confidence: 99%
“…For example Fuller et al [10] presented a "causality index" to compare incidental and lethal post-mortem drug concentrations using inferential statistics , Langford et al [11] described a Bayesian Network for the assessment of the probability of a death having been caused by the analytically determined blood concentration of drug(s). Biedermann et al [12], Taroni et al [13]and Bossers & Paul [14] used likelihood ratios for the interpretation of forensic cut-offs and legal thresholds and Woldegebriel et al [15]used Bayesian algorithms for the detection of compounds during unknown drug screening.…”
Section: Introductionmentioning
confidence: 99%